Descriptive Profile of Maternal Guilt Levels on Female ICU Nurses in South Borneo - Yulia Hairina; Nurul Hartini; Nursalam; Imadduddin (Future Science, 2024)
The purpose of this study was to describe the level of maternal guilt experienced by female intensive care unit (ICU) nurses in South Kalimantan, Indonesia. Maternal guilt is a common emotional experience among working mothers and often arises when women find it difficult to meet the dual demands of their professional responsibilities and the expectations associated with motherhood. Female ICU nurses, who work in a high-pressure environment with significant demands on their time and energy, are particularly vulnerable to experiencing this guilt due to the nature of their work, which requires constant vigilance and care for critically ill patients. This study was conducted using a descriptive survey design, involving 105 female ICU nurses from 11 hospitals in South Kalimantan. The study used the Maternal Occupational Guilt Scale (MEGS) to measure the level of maternal guilt. Findings showed that the majority of nurses surveyed reported experiencing moderate to high levels of maternal guilt. Those aged 30–39 years and those with two or three children were found to be particularly affected. This study highlights the need for targeted interventions to support female ICU nurses in managing their dual roles, with the potential for such initiatives to improve mental health outcomes and enhance the quality of care provided to patients. Furthermore, this study underscores the importance of understanding the cultural and social context of maternal guilt in South Kalimantan to develop effective and culturally sensitive strategies. A comprehensive understanding of this local context is essential to alleviate this emotional burden and support the well-being of these healthcare professionals.